К вопросу исследования характеристик форм кривых выходного напряжения структуры инвертор напряжения – асинхронный двигатель - Шокарев, Д. А.; Шокарьов, Д. А.; Shokarov, Dmytro (КНТУ, 2016)
В работе проведен анализ, позволяющий повысить качество выходного напряжения при формировании широтно-импульсной модуляции (ШИМ) путем использования трапецеидального сигнала за счет снижения числа коммутаций при синхронности моментов переключения силовых транзисторов во всех фазах инвертора. В роботі виконаний аналіз, який дозволяє підвищити якість вихідної напруги при формуванні широтно-імпульсної модуляціі (ШІМ) шляхом використання трапецеїдального сигналу за рахунок зниження числа комутацій при синхронності моментів перемикання силових транзисторів у всіх фазах інвертора. The analysis of the work leads to the conclusion that the formation of variants trapezoidal output voltage signal quality better by reducing the number of switching points during synchronous switching power transistors in all phases of the inverter. Increase the frequency of the carrier signal does not lead to the exclusion of a number of harmonic components of the output voltage, and to their movement toward higher frequencies. Therefore, an important moment in the formation of a variety of pulse width modulation switching frequency inverter power switches.
До питання дослідження характеристик форм кривих вихідної напруги структури інвертор напруги - асинхронний двигун
On the question of research of characteristics of the output voltage waveforms structure of a voltage inverter-induction motor
Keywords: широтно-импульсная модуляция; асинхронный двигатель; инвертор напряжения; несинусоидальность; широтно імпульсна модуляція; асинхронний двигун; інвертор напруги; несинусоідальність; pulse width modulation; asynchronous motor; the inverter voltage nonsinusoidality